2017
DOI: 10.1177/1479164117701876
|View full text |Cite
|
Sign up to set email alerts
|

The impact of smoking on the development of diabetes and its complications

Abstract: Diabetes is one of the most common metabolic disorders and emerges secondary to an interaction between genetic, environmental and lifestyle factors. This work provides an overview of the impact of smoking on the development of vascular complications in this condition and also provides an overview of the potential role of smoking in predisposition to diabetes. There are many studies documenting the impact of smoking on health (not focused on patients with diabetes), suggesting that the health exposure in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(127 citation statements)
references
References 109 publications
(175 reference statements)
1
114
2
10
Order By: Relevance
“…Recent data show tobacco use is higher among adults with chronic conditions (164) as well as in adolescents and young adults with diabetes (165). Smokers with diabetes (and people with diabetes exposed to second-hand smoke) have a heightened risk of CVD, premature death, microvascular complications, and worse glycemic control when compared with nonsmokers (166,167). Smoking may have a role in the development of type 2 diabetes (168-171).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Recent data show tobacco use is higher among adults with chronic conditions (164) as well as in adolescents and young adults with diabetes (165). Smokers with diabetes (and people with diabetes exposed to second-hand smoke) have a heightened risk of CVD, premature death, microvascular complications, and worse glycemic control when compared with nonsmokers (166,167). Smoking may have a role in the development of type 2 diabetes (168-171).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…The observation that low HDL‐C levels are an independent contributor of β‐cell function decline over time, coupled with the evidence that elevation of HDL‐C results in an improved insulin secretion in both patients with type 2 diabetes and healthy volunteers, raises the intriguing possibility that lifestyle and pharmacological interventions able to increase HDL‐C levels may not only improve glycaemic control in subjects with type 2 diabetes but also prevent or delay diabetes development in high‐risk subjects. Consistent with this view, there is evidence indicating that exercise training, quitting smoking and treatment with bezafibrate, a peroxisome proliferator‐activated receptor‐α agonist, all of which are associated with an increase in HDL‐C levels, may hamper type 2 diabetes onset.…”
Section: Discussionmentioning
confidence: 83%
“…It is well established that serious factors play an important role in developing DFU, such as decreased blood flow in extremities, peripheral angiopathy, and peripheral neu- ropathy, that are more common in smokers (13,25,26). Furthermore, some studies have reported that smoking aggravates glucose hemostasis and accelerates the onset and progress of microvascular and microvascular diabetes complications (27,28).…”
Section: Discussionmentioning
confidence: 99%